Microstructure and Mechanical Properties of Stainless Steel/Aluminum Multilayer Composites by One-Step Explosive Welding - Xiaoyan Hu; Yingbin Liu; Li Yang; Xiaochen Huang (Archives of Metallurgy and Materials, 2023)
The stainless steel/aluminum multilayer composites were prepared by one-step explosive welding using ammonium nitrate explosive with two different thicknesses. The microstructure and mechanical properties of the multilayer composites were examined. There is a thin metallurgical melting zone at each bonding interface, consisting mostly of iron and aluminum elements. However, the micro-crack appears in the second metallurgical bonding zone obtained using the explosive of 24 mm thickness. The micro-hardness values at the four bonding interfaces are higher than those of bulk 1060 aluminum and 304 stainless steel. The yield strength of the multilayer composites obtained in the two cases is higher than that of the original 304 stainless steel while the tensile strength is between those of the original 1060 aluminum and 304 stainless steel. Meanwhile, the tensile strength and yield strength of multilayer composites obtained by explosive welding with explosive of 20 mm thickness are relatively higher.